Biodiversity Inventory and Distribution of Metriorrhynchina Net-Winged Beetles (Coleoptera: Lycidae), with the Identification of Generic Ranges - Bocak, Ladislav; Motyka, Michal; Kusy, Dominik; Bilkova, Renata (Insects, 2020)
We reviewed the species-level classification of Metriorrhynchina net-winged beetles to make the group accessible for further studies. Altogether, 876 valid species are listed in a checklist along with known synonyms, combinations, and distribution data. The compilation of geographic distribution showed that Metriorrhynchina is distributed mainly in the Australian region with very high diversity in the islands at the northern edge of the Australian craton, i.e., in the Moluccas and New Guinea (54 and 423 spp. respectively). The neighboring northern part of the Australian continent houses a majority of known Australian species (112 spp.) and the diversity of net-winged beetles gradually decreases to the south (43 spp.). The fauna of Sulawesi is highly endemic at the generic level (4 of 10 genera, 67 of 84 spp.). Less Metriorrhynchina occur in the Solomon Islands and Oceania (in total 22 spp.). The Oriental Metriorrhynchina fauna consists of a few genera and a limited number of species, and most of these are known from the Philippines (51 of 94 Oriental spp.). We identified a high species level turn-over between all neighboring landmasses. The genus-level endemism is high in Sulawesi (4 genera) and New Guinea (11 genera), but only a single genus is endemic to Australia. During the compilation of the checklist, we identified some homonyms, and we propose the following replacement names and a new synonym: Metriorrhynchus pseudobasalis, nom. nov. for M. basalis Lea, 1921 nec M. basalis Bourgeois, 1911; Metriorrhynchus pseudofunestus, nom. nov. for M. funestus Lea, 1921 nec M. funestus (Guérin-Méneville, 1838), Trichalus pseudoternatensis, nom. nov. for T. ternatensis Kleine, 1930 nec T. ternatensis Bourgeois, 1900, Procautires subparallelus, nom. nov. for P. parallelus (Pic, 1926) nec P. parallelus (Bourgeois, 1883), and Cautires pseudocorporaali, nom. nov. for C. corporaali (Pic, 1921: 12), (formerly Odontocerus and Cladophorus) nec C. corporaali (Pic, 1921) (formerly Bulenides, later Cautires). Diatrichalus biroi Kleine, 1943, syn. nov. is proposed as a junior subjective synonym of D. subarcuatithorax (Pic, 1926). Altogether, 161 new combinations are proposed, and 47 species earlier placed in Xylobanus Waterhouse, 1879 transferred from Cautirina to Metriorrhynchina incertae sedis. The study clarifies the taxonomy of Metriorrhynchini and should serve as a restarting point for further taxonomic, evolutionary, and biogeographic studies.
Keywords: new combinations; distribution; new names; endemism; Australian region; taxonomy; diversity centers